Answer:
The missing value in the solution to
the equation will be:
Step-by-step explanation:
Given the equation
![y+2\:=-3\left(x\:-\:4\right)](https://tex.z-dn.net/?f=y%2B2%5C%3A%3D-3%5Cleft%28x%5C%3A-%5C%3A4%5Cright%29)
As the value of y = -2 is given.
so substituting the value y = -2 in the equation to find the missing value
![\left(-2\right)+2\:=-3\left(x\:-\:4\right)](https://tex.z-dn.net/?f=%5Cleft%28-2%5Cright%29%2B2%5C%3A%3D-3%5Cleft%28x%5C%3A-%5C%3A4%5Cright%29)
switch the sides
![-3\left(x-4\right)=\left(-2\right)+2](https://tex.z-dn.net/?f=-3%5Cleft%28x-4%5Cright%29%3D%5Cleft%28-2%5Cright%29%2B2)
![\mathrm{Remove\:parentheses}:\quad \left(-a\right)=-a](https://tex.z-dn.net/?f=%5Cmathrm%7BRemove%5C%3Aparentheses%7D%3A%5Cquad%20%5Cleft%28-a%5Cright%29%3D-a)
![-3\left(x-4\right)=-2+2](https://tex.z-dn.net/?f=-3%5Cleft%28x-4%5Cright%29%3D-2%2B2)
![-3\left(x-4\right)=0](https://tex.z-dn.net/?f=-3%5Cleft%28x-4%5Cright%29%3D0)
![\mathrm{Divide\:both\:sides\:by\:}-3](https://tex.z-dn.net/?f=%5Cmathrm%7BDivide%5C%3Aboth%5C%3Asides%5C%3Aby%5C%3A%7D-3)
![\frac{-3\left(x-4\right)}{-3}=\frac{0}{-3}](https://tex.z-dn.net/?f=%5Cfrac%7B-3%5Cleft%28x-4%5Cright%29%7D%7B-3%7D%3D%5Cfrac%7B0%7D%7B-3%7D)
![x-4=0](https://tex.z-dn.net/?f=x-4%3D0)
![x=4](https://tex.z-dn.net/?f=x%3D4)
Therefore, the missing value in the solution to
the equation will be:
The equation is y=x+2
Use the formula y=Mx+b
Answer:
x=
1/2
Step-by-step explanation:
6x+9=12
Step 1: Subtract 9 from both sides.
6x+9−9=12−9
6x=3
Step 2: Divide both sides by 6.
6x/6=
3
/6
And Your Answer Will Be:
x=
1/2